Current-induced viscoelastic topological unwinding of metastable skyrmion strings. Issue 1 (December 2017) - Kagawa, Fumitaka; Oike, Hiroshi; Koshibae, Wataru; Kikkawa, Akiko; Okamura, Yoshihiro; Taguchi, Yasujiro; Nagaosa, Naoto; Tokura, Yoshinori
Abstract In the MnSi bulk chiral magnet, magnetic skyrmion strings of 17 nm in diameter appear in the form of a lattice, penetrating the sample thickness, 10–1000 μm. Although such a bundle of skyrmion strings may exhibit complex soft-matter-like dynamics when starting to move under the influence of a random pinning potential, the details remain highly elusive. Here, we show that a metastable skyrmion-string lattice is subject to topological unwinding under the application of pulsed currents of 3–5 × 106  A m–2 rather than being transported, as evidenced by measurements of the topological Hall effect. The critical current density above which the topological unwinding occurs is larger for a shorter pulse width, reminiscent of the viscoelastic characteristics accompanying the pinning-creep transition observed in domain-wall motion. Numerical simulations reveal that current-induced depinning of already segmented skyrmion strings initiates the topological unwinding. Thus, the skyrmion-string length is an element to consider when studying current-induced motion. Understanding the dynamics of the skyrmion string lattice is the prerequisite for its potential application as next-generation information carriers. Here, the authors explore the topological unwinding of skyrmion string lattice under the application of current pulses.